2009
DOI: 10.1152/ajpendo.90613.2008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prolonged fasting and sustained lipolysis on insulin secretion and insulin sensitivity in normal subjects

Abstract: Salgin B, Marcovecchio ML, Humphreys SM, Hill N, Chassin LJ, Lunn DJ, Hovorka R, Dunger DB. Effects of prolonged fasting and sustained lipolysis on insulin secretion and insulin sensitivity in normal subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
32
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 52 publications
8
32
0
Order By: Relevance
“…These metabolic effects of acipimox were shown previously in chronic (for weeks) treatment studies enrolling non-insulin-dependent diabetes mellitus (26), hyperlipoproteinemic patients (32), or subjects with both diseases (11). More recently, acipimox has also been investigated in acute (a few days) treatment studies in normal and diabetic subjects, confirming promising improvements in insulin sensitivity and NEFA levels (24,26). In general, chronic treatments with acipimox have been used at daily doses greater (ϳ1,200 mg) than those tested in short-term studies (250 -500 mg).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…These metabolic effects of acipimox were shown previously in chronic (for weeks) treatment studies enrolling non-insulin-dependent diabetes mellitus (26), hyperlipoproteinemic patients (32), or subjects with both diseases (11). More recently, acipimox has also been investigated in acute (a few days) treatment studies in normal and diabetic subjects, confirming promising improvements in insulin sensitivity and NEFA levels (24,26). In general, chronic treatments with acipimox have been used at daily doses greater (ϳ1,200 mg) than those tested in short-term studies (250 -500 mg).…”
Section: Discussionsupporting
confidence: 57%
“…On the other hand, FFAs have been shown to potentially influence insulin-mediated functions by interfering with insulin receptor activation and downstream intracellular signaling pathways (20). The increase in plasma FFA levels might be mediated by both prolonged fasting (sustained lipolysis) and excessive fat intake (24). In the metabolic syndrome, the physiological FFA modifications are chronically exaggerated and might favor the final development of insulin resistance.…”
mentioning
confidence: 99%
“…The relationship between portal insulin and GH sensitivity of the liver Human and other mammals are capable of prolonged fasting because they can recruit and utilize lipid stores when they exhaust readily available carbohydrates (20)(21)(22). Prolonged fasting is associated with a gradual decline in hepatic IGF1 production, which makes teleological sense due to the insulin-like effects of IGF1.…”
Section: Animal Studies Of the Actions Of Gh Versus Igf1mentioning
confidence: 99%
“…To address whether insulin resistance is directly involved in reducing BAT activity and NST, a 48 to 60 h fasting period can be employed to induce insulin resistance in young, healthy individuals [17][18][19]. We have recently shown that this prolonged fasting leads to a 50% reduction in insulin sensitivity, as determined by the gold standard method, hyperinsulinaemic-euglycaemic clamp, probably due to increased NEFA levels and/or accumulation of triacylglycerols in peripheral tissues [18].…”
Section: Introductionmentioning
confidence: 99%